Lessons learned about virtual education during the COVID-19 pandemic - Faghir-Gangi, Monireh; Khezri, Rozhan; Mohammadpour, Yousef; Valizadeh, Rohollah (Investigación y Educación en Enfermería, 2023)
The COVID-19 pandemic has affected education systems worldwide and led to the closure of face-to-face education in schools and universities. Virtual education has been offered as an alternative to face-to-face teaching in educational centers. Virtual or online education is a type of formal education carried out with the help of electronic resources such as computers and the Internet.(1) In contrast, face-to-face education, in which the teacher is present in the classroom and communicates verbally with the students simultaneously, is held in fixed physical environments.